2021
DOI: 10.1002/iid3.396
|View full text |Cite
|
Sign up to set email alerts
|

RNA m6A methylation regulates virus–host interaction and EBNA2 expression during Epstein–Barr virus infection

Abstract: Introduction N6‐methyladenosine (m6A) is the most prevalent modification that occurs in messenger RNA (mRNA), affecting mRNA splicing, translation, and stability. This modification is reversible, and its related biological functions are mediated by “writers,” “erasers,” and “readers.” The field of viral epitranscriptomics and the role of m6A modification in virus–host interaction have attracted much attention recently. When Epstein–Barr virus (EBV) infects a human B lymphocyte, it goes through three phases: th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 44 publications
(107 reference statements)
2
33
0
Order By: Relevance
“…From our previous results 26 , we found that the m6A abundance was increased in ATM mRNA transcripts upon EBV infection (Figure 1 A). ATM is a key kinase in DNA damage response, which is responsible for detecting, transmitting and repairing DNA damage response 21 .…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…From our previous results 26 , we found that the m6A abundance was increased in ATM mRNA transcripts upon EBV infection (Figure 1 A). ATM is a key kinase in DNA damage response, which is responsible for detecting, transmitting and repairing DNA damage response 21 .…”
Section: Resultssupporting
confidence: 62%
“…Previous studies 23 - 25 including ours 26 have identified the effect of Epstein-Barr Virus (EBV) infection on the level of transcriptomic m6A modifications in host cells. Upon EBV infection, we identified increased levels of m6A modification of ATM mRNA.…”
Section: Introductionmentioning
confidence: 99%
“…Two recent studies reported that the EBV infection induces changes in N 6 -methyladenosine RNA methylation of viral and host cell mRNA. These epitransciptomic changes promoted EBV infection in vitro [ 391 , 392 ]. Once more, viruses take advantages of cellular processes to favor their life cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Although the m6A modification was identified during the latent stage of EBV infection, the modification of EBV transcripts by the deposition of m6A was reduced during lytic infection. Increased EBNA3C levels have been shown to increase the expression and stability of METTL14, which can induce the proliferation and colony formation of EBV-positive cells ( Zheng et al, 2021 ) and stabilize METTL3 via its interaction with RNAs ( Klungland and Dahl, 2014 ; He and He, 2021 ). METTL3 is highly expressed in nasopharyngeal carcinoma tissues and affects the overall survival of patients with nasopharyngeal carcinoma.…”
Section: Roles Of M6a Modification In Hnsccmentioning
confidence: 99%